The concept of "the people" in liberation theology - Menatsi, Richard (Rhodes University, Faculty of Divinity, Department of Divinity, 1994)
The concept of "the people" has become a key concept within the work of several Latin American theologians, Korean Minjung theologians and South African theologians. When liberation theologians use the concept of "the people" in their literature they do so with a lack of clarity, to the extent that the exact meaning of the term is obscure. In their usage of the concept "the people" liberation theologians come up with differing and at times contradictory meanings, particularly as regards the concrete and symbolic meanings of the concept. This thesis sets out to investigate the use of the concept "the people" by liberation theologians by consulting a selection from Latin American theology, Korean Minjung theology, South African liberation theology and Marxism, to detect its influence on the use of this notion. A general overview of the thesis indicates the following. The first chapter provides a detailed analysis of the concept of "the people" in the work of different liberation theologians. Chapter two considers "the people" in relation to poverty and oppression. The third chapter deals with "the people" as subjects of history. In the fourth chapter "the people" as a concept is developed in relation to belief within the Christian church. The final chapter is an evaluation. The thesis reveals that the following characteristics are central to "the people", they are poor and oppressed but are also inclusive of all those persons who identify and actively support the struggle against poverty and oppression. "The people" are subjects of their own history, finally they are Christian believers.
Keywords: Liberation theology; Poor -- Religious aspects; Poverty -- Religious aspects -- Christianity; Government, Resistance to -- Religious aspects -- Christianity